Publication date and author spelling for the hidden angelshark Squatina occulta - Faria, V. V. (2014)
Two dates of publication have been associated with the hidden angelshark Squatina occulta. Additionally, the name of the second author of this species has been cited with different spellings in different publications. Both inconsistencies are addressed in this study. It is suggested that the hidden angelshark be consistently cited as Squatina occulta Vooren & da Silva 1991.